Healthcare Utilization at Retirement: The Role of the Opportunity Cost of Time - Claudio Lucifora; Daria Vigani (Institute of Labor Economics (IZA), 2018)
We investigate the causal impact of retirement on healthcare utilization using SHARE data for 10 European countries. We show that the number of doctor's visits and the probability of visiting a doctor more than four times a year (our measures of healthcare utilization) increase after retirement. The increase in healthcare utilization is found to depend mainly on the years spent in retirement, suggesting that adjustment may take time. We find evidence of heterogeneous effects by gender and across different patterns of time use prior to retirement (i.e., working long hours, and combined work and out-of-work activities). Overall, the empirical findings suggest that the increase in healthcare utilization is consistent with the decrease in the opportunity cost of time faced by individuals when they retire.
Keywords: J26; I10; C26; 330; retirement; health; healthcare utilization